2010
DOI: 10.1007/s10690-010-9135-z
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Japanese Stock Returns with Financial Ratios and Other Variables

Abstract: This paper extends the previous analyses of the forecastability of Japanese stock market returns in two directions. First, we carefully construct smoothed market price-earnings ratios and examine their predictive ability. We …nd that the empirical performance of the price-earnings ratio in forecasting stock returns in Japan is generally weaker than both the price-earnings ratio in comparable US studies and the price dividend ratio. Second, we also examine the performance of several other forecasting variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…They find that the effect of book to market value ratio is positive on stock return whereas the impact of price to earnings ratio is not significant on stock return. Aono and Iwaisako (2011) compare the financial ratios as a predictor of market stock return between companies listed on US and Japan markets. They find that Japanese financial ratios as a predictor of market stock return is weaker than US financial ratios i.e., price to dividend ratio and price to earnings ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They find that the effect of book to market value ratio is positive on stock return whereas the impact of price to earnings ratio is not significant on stock return. Aono and Iwaisako (2011) compare the financial ratios as a predictor of market stock return between companies listed on US and Japan markets. They find that Japanese financial ratios as a predictor of market stock return is weaker than US financial ratios i.e., price to dividend ratio and price to earnings ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The value of the error statistic of the root mean of the in-sample forecasting performance of the Market Level Return is less than 1 and near to 0 which indicates the good in-sample forecasting fit statistic of the Market Value Financial Ratios to predict the Market Level Return. Similarly, the Error Statistics of the Bias Proportion, Covariance Proportion, and the Variance Proportion of the Mean Absolute Error turns out to be 1 which again strengthens the forecastability of the explanatory variables to predict the Market Level Return (Aono and Iwaisako, 2011). The rest of the forecast Error Statistics of Mean Absolute Error, as well as the Theil Inequality, also support predictability of the Market Return by the Market Value Financial Ratios which indicates that the investors may seek information from the Market Value Financial Ratios provided in the Audit Reports before turning in to the stock markets for investment purpose respectively.…”
Section: Mean Sd Skewness Kurtosis Jb-test P-valuementioning
confidence: 53%
“…Many studies Emamgholipour et al, (2013), Mirfakhr et al, (2011), Zeytinoglu et al, (2012), and Eitan and Oleemat (2015) have used market ratios to determine the valuation of stocks in the financial market. Aono & Iwaisako (2011) and Wijesundera et al,(2015) have used financial ratios in forecasting stock returns in developed markets respectively. It has been found that emerging markets usually have high stock returns as compared to developed markets due to noise, less transparent information, and expected market liquidity (Paddrik and Tompaidis 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Aono and Iwaisako [16] demonstrated that the influence of price earnings ratios is quite strong in USA, while this ratio exerts a weak influence on stock prices in Japan. Moreover, price earnings ratios differ from other ratios playing a crucial role in stock price, especially for smaller corporations [16]. On the same topic, Pech, Noguera and White [17] or Lewellen [18] find a close relationship between stock prices and ratios, such as dividend yield, earning per share, and book to market value of equity.…”
Section: Literature Reviewmentioning
confidence: 99%